KEBIJAKAN HUKUM PEMERINTAH PROVINSI DAERAH ISTIMEWA YOGYAKARTA DALAM MENINGKATKAN PENANAMAN MODAL DALAM NEGERI SEBAGAI UPAYA MENSTABILKAN PERTUMBUHAN EKONOMI DI DAERAH ISTIMEWA YOGYAKARTA - , Bustanul Arifin, SE; , Andi Sandi Antonius, T.T., S.H., LL.M ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of development is to improve the welfare of the community. Indonesia is a country building. In the development process, it takes alarge investment. Because of the importance of investment for DIY Province, expected that all parties to try to improve the attractiveness of regional investment in order to attract investors. Policy and determinants of investment that effect the investment should get special attention from the Government ofDIY. This research is a normative legal research. Data was obtained with literary study and field study. Data collection was done by direct research in field to look for information relevant to research object using direct interview. Primary and secondary data was analyzed quantitatively by categorizing data that related to each problem formulation. The research finds that: First, Policies that have been taken by the Government of DIY Province based on the mission stated in the Medium Term Regional Development Plan (RPJMD) and Long-Term Regional Development Plan (RPJPD). Second, The Barriers is Yogyakarta Provincial Government has not had full authority to investment, especially investment licensing. The authority of the investment is owned by the BKPM and the district/city overnment.